Ukrainian experience in the WISH programme as a tool for the development and professional growth of female tennis coaches - Ibraimova, M.; Khaniukova, O. (Coaching and Sport Science Review, 2024)
Development and training programmes for coaches of different qualifications have always been an integral and important part of the work of the International Tennis Federation (ITF). Most of them are aimed at improving the knowledge of coaches on training types, planning and organising the practice process of tennis players of different qualifications, as well as tutors of ITF courses for different continents. It is important to note that in recent years, the trend towards gender equality has been growing around the world, in various industries and in sports. Moving in step with the modern demands of society, the ITF cares about the decent opportunities for female coaches, their realisation and achievements. Female coaches often face various challenges and difficulties that affect their growth and development as professionals. The WISH programme (Women in Sport High-Performance Pathway Programme), supported by the ITF and Olympic Solidarity, is a completely new and innovative approach to training and assisting female coaches, and is aimed specifically at their personal development. The given article focuses on the experience of a WISH Cohort 2 participant and her specific mentor.